Access to higher education: much more than entering the system (2019)
Te problem of access to higher education (HE) continues to be a challenge for many countries in the world, just as it is for Colombia. Based on a literature review, there is no consensus on the concept of access, which can be related to the particular situation of HE systems in each country, and to the new approaches and interests that emerge. Tis study builds four notions of access from literature: entrance, representation, successful participation, and college choice. Te state of access to HE in Colombia is diferent depending on the notion that is selected, and it is suggested that by focusing only on one of them, relevant aspects are excluded. Finally, there is a need for a systemic understanding of HE, from which emerges a notion of access that focuses on the abilities and opportunities of people from the moment they develop an aspiration to HE until they achieve it.